AN EFFICIENT HEURISTIC METHOD FOR DETERMINING MULTI-ECHELON DISTRIBUTION QUANTITIES AND VEHICLE ROUTES - Chiu, Huan Neng; Lee, Yi S.; Hwang, Ming Hua (International Journal of Industrial Engineering: Theory, Applications and Practice, 2022)
This paper formulates a novel mixed-integer programming model for determining multi-echelon distribution quantities and vehicle routes simultaneously, and then develops an efficient two-phase heuristic method for solving large-scale problems. A good initial solution can be generated in the first phase heuristic, in which three important criteria are involved. The second phase heuristic, based on Luger’s best-first search method, is developed to improve the solution quality. The excellent performance ofthe proposed two-phase heuristic method is verified through two experiments.